THE LIVING MUSLIM ETHICS IN CHARACTER EDUCATION - Muhammad Muntahibun Nafis (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2019)
This paper examines character education as discussed through Kitab Adab al-‘Alim wa al-Muta’allim by the founder of the largest Muslim organization in Indonesia, Nahdlatul Ulama, Kiai Hasyim Asy’ari (1871-1947). It tries to locates character education as the transformation of Muslim subjects as the foundation of social piety. The article further argues that Kiai Hasyim Asy’ari through his work had laid a comprehensive Islamic values that are parallel to principles of character education. The core values of Islamic character education centers on the notions of rabbaniyah (godness), insaniyah (humanity), wasathiyyah (moderateness) and waqi’iyyah (reality). Therefore, Kitab Adab al-‘Alim wa al-Muta’allim reserves as a pesantren-based character education with a particular reference of creating a Muslim subject with social-piety element.